2009
DOI: 10.1177/0748233709106769
|View full text |Cite
|
Sign up to set email alerts
|

Mercury vapor inhalation and its effect on glutathione peroxidase in goldsmiths exposed occupationally

Abstract: In the gold ornaments manufacturing cottage industries, the gold metal grain dust waste particles are recovered from mercury (Hg) amalgam. The results on air samples from these industries during the recovery process have shown a high prevalence of Hg vapor (42.7 mg/m(3)). The blood concentration of Hg is elevated (79.1 microg/L) among workers when their blood samples are tested. The Hg toxicity is reflected in the reduction of glutathione peroxidase enzyme activity in RBC (49.317 mg/L of RBC) when compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In dental workers exposed to Hg 0 (B-Hg: 7.74 ± 1.03 μg/L vs 4.79 ± 0.84 μg/L in control subjects), a negative correlation was found between Hg exposure and GPx activity (40% reduction) in erythrocytes (Samir and Aref, 2011). However, for higher exposure levels (average B-Hg: 79.1 μg/L), Jayaprakash (2009) reported a reduction of only 30% in RBC GPx activity. Interestingly, Kobal et al (2008), found no marked differences in RBC GPx activity between former Hg miners (average U-Hg: 2.53 μg/g creatinine) and control subjects (average U-Hg: 1.31 μg/g creatinine), even though Se excretion was higher in miners as evidenced by lower plasma and higher urinary Se (Kobal et al, 2004).…”
Section: New Perspectives: Mechanistic-based Biomarkersmentioning
confidence: 91%
“…In dental workers exposed to Hg 0 (B-Hg: 7.74 ± 1.03 μg/L vs 4.79 ± 0.84 μg/L in control subjects), a negative correlation was found between Hg exposure and GPx activity (40% reduction) in erythrocytes (Samir and Aref, 2011). However, for higher exposure levels (average B-Hg: 79.1 μg/L), Jayaprakash (2009) reported a reduction of only 30% in RBC GPx activity. Interestingly, Kobal et al (2008), found no marked differences in RBC GPx activity between former Hg miners (average U-Hg: 2.53 μg/g creatinine) and control subjects (average U-Hg: 1.31 μg/g creatinine), even though Se excretion was higher in miners as evidenced by lower plasma and higher urinary Se (Kobal et al, 2004).…”
Section: New Perspectives: Mechanistic-based Biomarkersmentioning
confidence: 91%
“…Mercuric chloride (HgCl2) is one of the environmental pollutants that are currently used as a catalyst or reagent in various chemical reactions, and to a lesser extent as a disinfectant or pesticide it is also a developmental toxicant in experimental animals following both oral and inhalation exposure (US EPA., 1984). Mercury is nonbiodegradable and non-advantageous heavy metals and their role in the cell is not understood (Bailey S. E et al,1999).The soil with methyl mercury contamination or water with mercury methyl chemical species is easily absorbed by aquatic organisms, because of its strong affinity of sulfhydryl biopolymers such as proteins (Jayaprakash, K. 2009). Human destructive influence on the aquatic environment in the form of sub-lethal pollution usually results in chronic stress conditions that have negative influence on aquatic life (P.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Exposure to HgO used in dental clinics as filling material, in the atmosphere, and in various occupations has an adverse influence on body health . It is thought that Hg suppresses the DNA repair mechanisms and molecular mechanisms, resulting in cell damage, increased lipid peroxidation products, and decreased glutathione peroxidase enzyme activity . Also, the toxicity of Hg could attenuate the activity of antioxidant enzymes, and impair mitochondrial function …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] It is thought that Hg suppresses the DNA repair mechanisms and molecular mechanisms, resulting in cell damage, increased lipid peroxidation products, and decreased glutathione peroxidase enzyme activity. 32,33 Also, the toxicity of Hg could attenuate the activity of antioxidant enzymes, and impair mitochondrial function. 34,35 Given the ability of Hg to spread into tissue, the reproductive system in female individuals is susceptible to disorders following exposure to Hg.…”
Section: Discussionmentioning
confidence: 99%